Nano Online 2016
DOI: 10.1515/nano.12951_2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Lactosaminated mesoporous silica nanoparticles for asialoglycoprotein receptor targeted anticancer drug delivery

Abstract: Background: Mesoporous silica nanoparticles (MSNs) have several attractive properties as a drug delivery system, such as ordered porous structure, large surface area, controllable particle size as well as interior and exterior dual-functional surfaces. The purpose of this study was to develop novel lactosaminated mesoporous silica nanoparticles (Lac-MSNs) for asialoglycoprotein receptor (ASGPR) targeted anticancer drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Therefore, the specific endocytotic pathways for Lf-PLS in the different HCC cell lines should be explored. 39 Similar to cellular uptake, cytotoxicity effects of nanoparticles strongly depend on the material, solubility and release of toxic drugs, cell types, and incubation times, etc. 40,41 Previously, empty PLS and Lf-PLS were demonstrated to have good tolerability and low toxicity in target cells (HepG2) and normal cells (ECV 304).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the specific endocytotic pathways for Lf-PLS in the different HCC cell lines should be explored. 39 Similar to cellular uptake, cytotoxicity effects of nanoparticles strongly depend on the material, solubility and release of toxic drugs, cell types, and incubation times, etc. 40,41 Previously, empty PLS and Lf-PLS were demonstrated to have good tolerability and low toxicity in target cells (HepG2) and normal cells (ECV 304).…”
Section: Discussionmentioning
confidence: 99%
“…38 To clarify these phenomena, the specific endocytotic pathways for Lf-PLS in different HCC cell lines should be explored. 39 …”
mentioning
confidence: 99%
“…Outer decoration of MSNs with disulphide linked polymer to achieve the redox responsive release of drug has been done by author Liu R, et al 78 A variety of functional group or moieties can be attached on the surface of MSNs by either of the above mentioned techniques as listed in the Table 2. 11,[79][80][81][82][83][84][85][86][87][88][89][90] Backfilling strategy is another approach used for MSNs fabrication. It is a simple approach to introduce active molecules into the empty pores of mesostructured silica wherein, these empty pores are exposed to the solution or vapour of active molecules and are allowed to diffuse.…”
Section: Post Synthesis Strategymentioning
confidence: 99%
“…10 Mesoporous silica nanoparticle (MSNs) is one of the nano carriers, which are in focus for targeting the tumor cells. 10,11 MSNs based targeted delivery offers a promising tool for increasing the intra tumoral concentration of anticancer drugs and limiting its toxic effects to normal cells as they bind to cell membrane receptors which are over expressed in cancer cells only. This has led to a great research interest towards targeting the drug loaded MSNs into tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…So some researchers have developed an effective lipid-coated MSN platform for synergistic delivery of Gemcitabine and paclitaxel to human pancreatic cancer [65]. Guilan Quan et al [66] demonstrated that lactosaminated MSNs are promising inorganic carrier systems for asialoglycoprotein receptor-targeted anticancer drug delivery [66]. MSNs are highly interesting for gene delivery applications [67].…”
Section: Other Applicationsmentioning
confidence: 99%